Juridical Review of the Role of the Makassar Heritage Hall in Issuing Certificates of Inheritance - Andi Muhammad Fikri Ramadani Andi Nganro; La Ode Husen; Dian Eka Pusvita Azis (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
This study aims to analyze the legal force of the certificate of inheritance issued by the Balai Harta Peninggalan (Inheritance Affairs Office) in Makassar City, as well as the responsibilities of the office regarding the issuance of such certificates. The research employs a normative juridical method with legislative, conceptual, and case study approaches. The data used consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The results show that the certificate of inheritance issued by the Inheritance Affairs Office holds legal validity as long as it meets the requirements stipulated in the applicable laws and regulations. However, in practice, the implementation of this authority encounters several challenges, including inconsistencies in data that may affect the legitimacy of the certificate. Furthermore, the Inheritance Affairs Office bears full responsibility for ensuring the accuracy and validity of the information used as the basis for issuing the certificate, including being held accountable in cases of disputes arising from the issued documents. The recommendation of this study is to contribute to strengthening the understanding of the role and responsibilities of the Inheritance Affairs Office within the Indonesian inheritance law system.  Abstrak : Penelitian ini bertujuan untuk menganalisis kekuatan hukum surat keterangan waris yang diterbitkan oleh Balai Harta Peninggalan di Kota Makassar, serta tanggung jawab lembaga tersebut dalam penerbitan surat keterangan tersebut. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan studi kasus. Data yang digunakan terdiri atas bahan hukum primer, sekunder, dan tersier, yang dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa surat keterangan waris yang diterbitkan oleh Balai Harta Peninggalan memiliki kekuatan hukum sepanjang memenuhi persyaratan yang ditetapkan dalam peraturan perundang-undangan yang berlaku. Namun, dalam praktiknya, pelaksanaan kewenangan tersebut menghadapi beberapa kendala, antara lain ketidakkonsistenan data yang dapat memengaruhi keabsahan surat keterangan tersebut. Selain itu, Balai Harta Peninggalan memikul tanggung jawab penuh untuk memastikan keakuratan dan keabsahan informasi yang dijadikan dasar penerbitan surat, termasuk pertanggungjawaban dalam hal terjadi sengketa yang timbul akibat dokumen yang diterbitkan. Rekomendasi dari penelitian ini adalah memberikan kontribusi dalam memperkuat pemahaman mengenai peran dan tanggung jawab Balai Harta Peninggalan dalam sistem hukum waris di Indonesia